Evolution versus entrenchment: Debating the impact of digitization, democratization and diffusion in the global fashion industry. (1st October 2018) - Brydges, Taylor; Hracs, Brian J.; Lavanga, Mariangela
In the report The State of Fashion 2017, written by Business of Fashion and the McKinsey Institute (2016), industry executives used three words to describe the current state of the fashion industry: uncertain, changing and challenging. Indeed, the fashion industry is undergoing dramatic transformations, from digitization and the rise of 'see now, buy now' fashions, to brands redefining the function and timing of fashion weeks, and increasing levels of global integration and competition (Crewe 2017). As such, the fashion industry has been recognized as a valuable lens through which to explore significant and ongoing changes to the production, curation and consumption of goods, services, and experiences (Brydges et al. 2014; Brydges 2017; D'Ovidio 2015; Hracs et al. 2013; Lavanga 2018; McRobbie 2016; Pratt et al. 2012).Drawing inspiration from this stream of scholarship, we organized four sessions titled Trending Now: The Changing Geographies of Fashion in the Digital Age at the Royal Geographical Society and Institute of British Geographers (RGS-IBG) conference in London, 30 August – 1 September 2017. In these sessions, researchers and practitioners from a wide range of locations and disciplines – including fashion studies, media studies, cultural economics, business and geography – came together to share research related to the structures, labour dynamics, spaces, value propositions and practices of the contemporary fashion industry.While a range of issues were discussed, the sessions were connected by an overarching theme. Namely, the extent to which power in the fashion industry is expanding or consolidating. While there is a prominent discourse that states that structures, systems and spaces within the global fashion industry have been (and will continue to be) disrupted by new actors, technologies, practices and cities, we collectively questioned whether the fashion industry has really entered an era of democratization, or if established power structures remain entrenched. Through empirical case studies from a variety of geographic contexts – from India to Italy – about different actors and activities within the industry, each presentation contributed new evidence and perspectives to this debate. The discussion below distils some of the key themes that emerged.